Pengaruh kualitas Pelayanan, Kepercayaan Nasabah dan Teknologi Sstem Informasi Terhadap Kepuasan Nasabah di PT. TASPEN Cabang Padang - Dewi Zulvia; Krisvia Krisvia (Jurnal Ilmiah Pendidikan Scholastic, 2021)
The key competitive advantage in a situation full of competition is the ability of the company in improving customer satisfaction. Customer satisfaction will be the key to success, not only in the short term but sustainable competitive advantage. The purpose of this research is to find out and analyse the influence the service quality, trust and technology information system on customer satisfaction in Taspen (Persero) compayny of Padang. Technique data collecting in this research use the questionnaire. The sample taken by as much 100 people customers at PT. Taspen (Persero) Branch the Padang by using scale likert. Design research is quantitative with the hypothesis. Data analysis techniques using multiple linear regression using SPSS 25. This result indicates that the variable of 1) service quality have an effect on positive to customer satisfaction 2) trust have an effect on positive to customer satisfaction 3) technology information system have an effect on positive to customer satisfaction